Body Composition of Bangladeshi Children: Comparison and Development of Leg-to-Leg Bioelectrical Impedance Equation - Khan, Ashraful I; Hawkesworth, Sophie; Hawlader, Mohammad Delwer Hossain; Arifeen, Shams El; Moore, Sophie; Hills, Andrew P; Wells, Jonathan C; Persson, Lars-Åke; Kabir, Iqbal (Journal of Health, Population and Nutrition, 2012)
The aim of this study was to investigate the validity of the Tanita TBF 300A leg-to-leg bioimpedance analyzer for estimating fat-free mass (FFM) in Bangladeshi children aged 4-10 years and to develop novel prediction equations for use in this population, using deuterium dilution as the reference method. Two hundred Bangladeshi children were enrolled. The isotope dilution technique with deuterium oxide was used for estimation of total body water (TBW). FFM estimated by Tanita was compared with results of deuterium oxide dilution technique. Novel prediction equations were created for estimating FFM, using linear regression models, fitting childs height and impedance as predictors. There was a significant difference in FFM and percentage of body fat (BF%) between methods (p<0.01), Tanita underestimating TBW in boys(p=0.001) and underestimating BF% in girls (p<0.001). A basic linear regression model with height and impedance explained 83% of the variance in FFM estimated by deuterium oxide dilution technique. The best-fit equation to predict FFM from linear regression modelling was achieved by adding weight, sex, and age to the basic model, bringing the adjusted R2 to 89% (standard error=0.90, p<0.001). These data suggest Tanita analyzer may be a valid field-assessment technique in Bangladeshi children when using populationspecific prediction equations, such as the ones developed here. DOI: http://dx.doi.org/10.3329/jhpn.v30i3.12291 J HEALTH POPUL NUTR 2012 Sep;30(3):281-290